Bamboo Fiber Reinforced Chemically Functionalized Acrylonitrile Butadiene Styrene Composites by Palsule Process. Issue 1 (31st December 2023) - Kumar, Piyush; Palsule, Sanjay
ABSTRACT: Bamboo fibers (BBF) and reinforced chemically functionalized acrylonitrile-butadiene-styrene (CF-ABS) composites (BBF/CF-ABS) have been processed up to 190ºC, extending Palsule process to higher processing temperatures. The composites show higher tensile and flexural properties than CF-ABS. BBF act as stress concentrators, reduce deformation and thus impact strength of the composites relative to the matrix. Esterification reaction and hydrogen bonds are formed between BBF and CF-ABS at higher processing temperatures also, and these bonds impart adhesion between them in the composites. Thermal stability of the BBF/CF-ABS composites is between those of BBF and CF-ABS, and their degradation starts above 270ºC. The composites show better mechanical properties than the same composite by the fiber treatment, the compatibilizer and their combined processes. SUMMARY: Palsule process has been used for composites requiring lower processing temperatures only. The process is extended to higher processing temperatures for bamboo fibers/CF-ABS composites. This study establishes fiber/matrix adhesion by the process at higher processing temperatures. The composites show higher mechanical properties except impact strength than CF-ABS. Shows advantages of Palsule process over fiber treatment and compatibilizer processes.